The Role of the Anonymous Voice in Post-Publication Peer Review Versus Traditional Peer Review - Jaime A. Teixeira da Silva; Judit Dobránszki (KOME: An International Journal of Pure Communication Inquiry)
Traditional peer review (TPR) has several limitations and weaknesses. Post-publication peer review is one practical way to repair the ills of TPR and reinforce it. A literature that is marked by errors is unhealthy and should, if given the opportunity, be corrected or further improved. The anonymous voice is one source of critique and differs from the blind peer review in TPR in which the reviewer remains anonymous to the authors and/or vice versa, but the identity is known to the editor. If unregulated, the anonymous voice can pose a threat to established editorial norms in TPR, to one of the most important criteria of science publishing, i.e., transparency, and to worthwhile discussion. Yet, if the anonymous voice is not heard, then a vast and potentially valuable pool of untapped opinions may be lost, opinions that may provide valuable solutions to improving TPR.